Meals, music, and muses : recipes from my African American kitchen - Smalls, Alexander, 1952-; Chambers, Veronica (Flatiron Books, 2020)
"Alexander Smalls has owned, conceptualized, and helmed some of New York's most iconic African American restaurants. Now, he follows up the James Beard award-winning Between Harlem and Heaven with Meals, Music, and Muses, a look at his world glimpsed through the lenses of music, food, culture, and history. It is a must-read journey through a life well lived and in recipe and reminiscence details the musical forms learned, the friends and family who instructed, and the foods shared along the way." Jessica B. Harris "If wine is bottled poetry, and jazz is brown sugar sprinkled in your ear, then Meals, Music, and Muses is a smorgasbord of fine words and sounds, a delicious symphony of haute cuisine that'll make you wanna kiss your momma, then thank the ancestors for making a way out of no way-for Hoppin' John Cakes and Grits and Sage Sausage Gravy and Frogmore Stew and all the recipes Alexander Smalls has reimagined so elegantly." Kwame Alexander "I had the great honor of being a guest at one of Alexander's famous Sunday brunches in his beautiful brownstone in Harlem. The food was unbelievably delicious! It was a magical afternoon that I will never forget." Tina Knowles-Lawson "In Meals, Music, and Muses, Alexander creates a lyrical culinary anthology of our lives. A symphonic composition full of stories, contemporary southern recipes that celebrates the food and musical genres that influenced the history of America... He sets the table in a unique way from jazz to blues to divas on a plate...This is not your mother's cookbook..." Dee Dee Bridgewater"--